Effects of filter materials on the removal efficiency of phosphorus and nitrogen from wastewater in an enhanced AO-BAF system - Zichun YAN; Nosakhare Iseghayan (Kuwait Journal of Science)
Phosphorus and nitrogen are some of the major nutrients easily found in waste water that pollutes our water bodies resulting to eutrophication. For years, economical and effective ways have being sort after to reduce the influx of these nutrients into our water waters. Biological Aerated Filter (BAF)technology have been one of them, but some challenges have been found to affect the removal efficiency of phosphorus and nitrogen through the use of an ordinary AO BAF system. In that, the effluents from a normal AO BAF system hardly meets the environmental standard of effluents discharge into the local water bodies.